Effects of land‐use change in the Amazon on precipitation are likely underestimated. (17th August 2021) - Baudena, Mara; Tuinenburg, Obbe A.; Ferdinand, Pendula A.; Staal, Arie
Abstract: The Amazon forest enhances precipitation levels regionally as trees take up water from the soil and release it back into the atmosphere through transpiration. Therefore, land‐use changes in the Amazon affect precipitation patterns but to what extent remains unclear. Recent studies used hydrological and atmospheric models to estimate the contribution of tree transpiration to precipitation but assumed that precipitation decreases proportionally to the transpired portion of atmospheric moisture. Here, we relaxed this assumption by, first, relating observed hourly precipitation levels to atmospheric column water vapor in a relatively flat study area encompassing a large part of the Amazon. We found that the effect of column water vapor on hourly precipitation was strongly nonlinear, showing a steep increase in precipitation above a column water vapor content of around 60 mm. Next, we used published atmospheric trajectories of moisture from tree transpiration across the whole Amazon to estimate the transpiration component in column water vapor in our study area. Finally, we estimated precipitation reductions for column water vapor levels without this transpired moisture, given the nonlinear relationship we found. Although loss of tree transpiration from the Amazon causes a 13% drop in column water vapor, we found that it could result in a 55%–70% decrease in precipitation annually. Consequences of this nonlinearity might be twofold: although the effects of deforestation may be underestimated, it also implies that forest restoration may be more effective for precipitation enhancement than previously assumed. Abstract : Forests in the Amazon affect precipitation via transpiration. We find that the relationship of atmospheric water vapor with observed precipitation events is strongly nonlinear. This implies that loss of atmospheric moisture due to forest loss has disproportionate effects on regional precipitation: A complete loss of the Amazon forest would lead to a 55%–70% decrease of the precipitation annually.